2014
DOI: 10.3390/nu6093734
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Risk of Gastric Cancer: A Large Updated Meta-Analysis of Prospective Studies

Abstract: The potential role of coffee consumption in the development of various types of cancer has been extensively investigated in epidemiologic studies. How coffee consumption may modulate risk of gastric cancer, however, remains a subject open for investigation. To better quantify this relation, we quantitatively summarized evidence from prospective studies. Eligible studies were identified on PubMed databases. The summary risk estimates were obtained using the random-effects model. Subgroup, sensitivity and dose-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Although some researchers have a negative view of the relationship between smoking and an increased risk of gastric cancer, 56 others have an affirmative view, 57,58 and the IARC refers to smoking as a carcinogen with sufficient evidence. Three meta‐analyses on the intake of coffee and risk of gastric cancer showed inconsistent results: one suggested that the intake of coffee is related to a decrease in the risk of gastric cancer, 59 another showed no correlation, 60 and the remaining one showed no correlation but suggested involvement in an increased risk of gastric cardiac cancer 61 . Similar results were obtained for the intake of green tea.…”
Section: [I] Risk Stratification Of Gastric Cancer Before Endoscopic mentioning
confidence: 80%
“…Although some researchers have a negative view of the relationship between smoking and an increased risk of gastric cancer, 56 others have an affirmative view, 57,58 and the IARC refers to smoking as a carcinogen with sufficient evidence. Three meta‐analyses on the intake of coffee and risk of gastric cancer showed inconsistent results: one suggested that the intake of coffee is related to a decrease in the risk of gastric cancer, 59 another showed no correlation, 60 and the remaining one showed no correlation but suggested involvement in an increased risk of gastric cardiac cancer 61 . Similar results were obtained for the intake of green tea.…”
Section: [I] Risk Stratification Of Gastric Cancer Before Endoscopic mentioning
confidence: 80%
“…A recent similar meta-analysis included papers published before June 2014 and was published in September 2014 [ 4 ]. This meta-analysis pooled the relative risks comparing the highest versus lowest categories of coffee intake to obtain a summary estimate.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has suggested that there was no statistically significant association between coffee consumption (highest vs. lowest consumption) and the risk of gastric cancer [ 4 ]. However, the meta-analysis included studies with different outcome measures (morbidity or mortality) and pooled studies with different coffee consumption categories.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, metaanalyses conducted for colorectal, colon and rectal cancers (33-35, 50, 65, 141); breast cancer (52,69,119,141); and pancreatic cancer (31,96,104,123,141) showed differences in the statistical significance of the effects, but not in the direction. Moreover, increments in statistical significance or changes in the direction of the association were found in meta-analyses of oral or laryngeal cancer (16,98,124), atrial fibrillation (caffeine exposure) (14,21), gastric cancer (3,27,67,76,112,135,136,143), bladder cancer (43,134,141,154), and Alzheimer's disease and cognitive disorders (caffeine exposure) (58, 79, 109) (Supplemental Table 1).…”
Section: Figurementioning
confidence: 99%